Islamic Economics Perspectives on Investing in Sharia Mutual Funds Using Bibit Applications - Rizkia, Rini; Ichsan, Ichsan; Fuadi; Munardi (Institut Agama Islam Negeri Lhokseumawe, 2024)
The objective of this study is to examine the regulatory framework governing the implementation of Islamic economics principles in Sharia mutual funds on the Bibit platform. This study employs qualitative research methodologies to conduct descriptive research. The data gathering procedures involve the processes of observation, interviewing, and documentation. The data's credibility is assessed by the method of triangulation. Based on the findings of the research, it has been determined that investing in Sharia mutual funds in Islam is permissible, provided that they adhere to Islamic law without any deviations. According to the current fatwa, the use of Bibit for mutual fund investment is in accordance with Islamic law regulations on Sharia mutual fund products. These products provide investors with a mechanism that ensures their investments are free from usury and undergo a cleansing and screening process.